Nonlocal fluid mechanics description of solvation forces. (April 2016) - Okada, Kanzo; Sugiyama, Masaru
Abstract: In this paper an analytical expression for the solvation force, based on the nonlocal surface stress due to the nonlocal density variation, is constructed by making a surface functional approximation to the general stress constitutive equation of nonlocal viscous fluids. It is then applied to derive a well-known semi-empirical expression for solvation forces.